2018
DOI: 10.1186/s13287-018-0921-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from acellular Wharton’s jelly of the human umbilical cord promotes skin wound healing

Abstract: BackgroundCompromised wound healing has become a global public health challenge which presents a significant psychological, financial, and emotional burden on patients and physicians. We recently reported that acellular gelatinous Wharton’s jelly of the human umbilical cord enhances skin wound healing in vitro and in vivo in a murine model; however, the key player in the jelly which enhances wound healing is still unknown.MethodsWe performed mass spectrometry on acellular gelatinous Wharton’s jelly to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…EVs isolated from vector controls accelerated wound closure ( Fig. 4C, blue squares), consistent with reports showing that EVs accelerate wound closure (36,(59)(60)(61). In contrast, we observed that TBC1D3-regulated EVs failed to accelerate healing (Fig.…”
Section: Adoptive Transfer Of Tbc1d3-evs Delays Wound Closuresupporting
confidence: 91%
“…EVs isolated from vector controls accelerated wound closure ( Fig. 4C, blue squares), consistent with reports showing that EVs accelerate wound closure (36,(59)(60)(61). In contrast, we observed that TBC1D3-regulated EVs failed to accelerate healing (Fig.…”
Section: Adoptive Transfer Of Tbc1d3-evs Delays Wound Closuresupporting
confidence: 91%
“…This study also described that the effects of the EV were due, at least in part, to their high content of alpha-2-macroglobulin. Nevertheless, they did not identify the mechanisms by which this protein may act in wound healing (Bakhtyar et al, 2018).…”
Section: Fibroblastsmentioning
confidence: 99%
“…Indeed, MSC derivatives (Fig. 2) have, in some cases, been shown to be as therapeutically beneficial as living MSCs [30–33], but have the advantage of being able to pass easily through the circulatory system.…”
Section: Live Cells Dead Cells and Derivativesmentioning
confidence: 99%